Relative Investigation of Ant Colony Optimization and Genetic Algorithm based Solution to Travelling Salesperson Problem - Chandel, Ashwani; Singh, Vikram Jeet (International Journal of Computer Sciences and Engineering, 2015)
Travelling salesperson problem is a nondeterministic polynomial hard problem in combinatorial optimization studied in Operations Research and theoretical computer science. To solve this problem, we used two popular meta-heuristics techniques-Ant Colony Optimization and Genetic Algorithm. Both techniques are applied to solve a TSP with same dataset. We then compare them. For Ant Colony Optimization, we studied the effect of some parameters (number of ants, evaporation and number of iterations) on the produced results. On the other hand, we studied chromosome population, crossover probability and mutation probability parameters that effect Genetic Algorithm results.